2004
DOI: 10.1007/s00526-003-0241-x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal nodal solutions of the pure critical exponent problem on a symmetric domain

Abstract: We establish existence of nodal solutions to the pure critical exponent problem −∆u = |u| 2 * −2 u in Ω, u = 0 on ∂Ω, where Ω a bounded smooth domain which is invariant under an orthogonal involution of R N . We extend previous results for positive solutions due to Coron, Dancer, Ding, and Passaseo to existence and multiplicity results for solutions which change sign exactly once. (2000): 35J65, 35J20 Mathematics Subject Classification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…The first such result was pointed out by Marchi and Pacella [13] for domains with thin tunnels. For symmetric domains with a small hole existence of a sign changing solution was shown by Clapp and Weth in [5] and their method applies also to get the result of [13]. Recently Musso and Pistoia [14] proved that, if the domain has certain symmetries and a small hole whose boundary is a sphere, then the number of sign changing solutions becomes arbitrarily large as the radius of the sphere goes to zero.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The first such result was pointed out by Marchi and Pacella [13] for domains with thin tunnels. For symmetric domains with a small hole existence of a sign changing solution was shown by Clapp and Weth in [5] and their method applies also to get the result of [13]. Recently Musso and Pistoia [14] proved that, if the domain has certain symmetries and a small hole whose boundary is a sphere, then the number of sign changing solutions becomes arbitrarily large as the radius of the sphere goes to zero.…”
Section: Introductionmentioning
confidence: 91%
“…Later a remarkable result was obtained by Bahri and Coron [1] who showed that the same holds for any R. In fact, they showed that (℘ ) has at least one positive solution in every domain having nontrivial homology with Z/2-coefficients. This last condition is, however, not necessary: examples of contractible domains for which problem (℘ ) has a solution have been given, for example, in [5,9,10,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…If the domain has several holes, Rey in [42] and Li-YanYang in [30] constructed solutions blowing-up at the centers of the holes as the size of the holes goes to zero. On the other hand, Clapp-Weth in [15] found a second solution to (C)ǫ, but they were unable to say if it was positive or changed sign. Clapp-Musso-Pistoia in [14] found positive and sign changing solutions to (C)ǫ blowing-up at the center of the hole and at one or more points inside the domain as ǫ goes to zero.…”
Section: Uǫ(x)mentioning
confidence: 97%
“…This bound has been used in some papers to obtain existence and multiplicity results for solutions of (1.3), see e.g. [16,17,24]. The proof of Lemma 1.1 is easy, and it is given for instance in [39, p.185].…”
Section: Lemma 11 (Energy Doubling Of Sign Changing Solutions) Everymentioning
confidence: 99%
“…A fascinating correlation between the solvability of (1.3) and geometric properties of was discovered by Bahri and Coron [5,19], and their work stimulated immense further research. We refer the reader to [21,26,33] for classical results and to [6,9,17], including the references given therein, for more recent developments.…”
Section: Introductionmentioning
confidence: 99%